2015
DOI: 10.1002/chem.201500788
|View full text |Cite
|
Sign up to set email alerts
|

Organometallic Probe for the Electronics of Base‐Stabilized Group 11 Metal Cations

Abstract: A number of trimetalloborides have been synthesized through the reactions of base-stabilized coinage metal chlorides with a dimanganaborylene lithium salt in the hope of using this organometallic platform to compare and evaluate the electronics of these popular coinage metal fragments. The adducts of Cu(I), Ag(I), and Au(I) ions, stabilized by tricyclohexylphosphine (PCy3), N-1,3-bis(4-methylphenyl)imidazol-2-ylidene (ITol), or 1-(2,6-diisopropylphenyl)-3,3,5,5-tetramethylpyrrolidin-2-ylidene (CAAC), with [{Cp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 90 publications
(64 reference statements)
1
18
0
1
Order By: Relevance
“…We isolated 1 – 3 by following previously reported procedures for related copper(I) CAAC complexes ,. However, we found that 4 – 6 , unlike their stable CAAC Et congeners,, rapidly decompose during the purification and recrystallization processes, despite the use of an inert atmosphere, and even in the solid state, giving 1 – 3 and free CAAC Me ligand. We were able to confirm the assumed identities of 4 – 6 by isolation of some single crystals, which also decomposed after some time, but were sufficiently stable for X‐ray diffraction analysis (see the Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…We isolated 1 – 3 by following previously reported procedures for related copper(I) CAAC complexes ,. However, we found that 4 – 6 , unlike their stable CAAC Et congeners,, rapidly decompose during the purification and recrystallization processes, despite the use of an inert atmosphere, and even in the solid state, giving 1 – 3 and free CAAC Me ligand. We were able to confirm the assumed identities of 4 – 6 by isolation of some single crystals, which also decomposed after some time, but were sufficiently stable for X‐ray diffraction analysis (see the Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
“…The compounds [CuX(CAAC Me )] (X=Cl ( 1 ), Br ( 2 ), I ( 3 )), [Cu(CAAC Me ) 2 ]X (X=Cl ( 4 ), Br ( 5 ), I ( 6 ), PF 6 ( 7 )), [Cu(CAAC Me )(N^N)]PF 6 (N^N=2,2′‐bipyridine ( 8 ), 1,10‐phenanthroline ( 9 )), and [Cu 2 (μ‐SPh) 2 (CAAC Me ) 2 ] ( 10 ) were prepared according to Scheme . We isolated 1 – 3 by following previously reported procedures for related copper(I) CAAC complexes ,.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Copperh alide and pseudo-halide complexes:C opper(I) halide and pseudo-halidec omplexesw ith ligands Me2 L, Et2 La nd Ad L were prepared as shown in Scheme 1, by combining as olution of the respective CAAC ligandsw ith coppers alts in THF,f ollowing procedures previously established for gold halide complexes. [10,11] While this work was in progress, the syntheses of ( Me2 L)CuCl and ( Et2 L)CuClw ere reportedi ndependently; [12] the compounds are included in Scheme 1f or the sake of completeness.A lthough the reactiono f Me2 Lw ith CuCl is essentially quantitative, the yields of ( Me2 L)CuX (X = Br,I )are moderate due to the formationo fi nsoluble by-products. However,h igh yields of the bromo and iodo complexes can be obtained by metathesis of ( Me2 L)CuClw ith NaBr or NaI, respectively.A n excess of Me2 La ffords the 2:1c omplex [( Me2 L) 2 Cu]I.T he halide complexes show good solubility in polar non-protic solvents like dichloromethane, THF, MeCN, DMF or acetonea nd are moderately soluble in toluene or ethanol but insoluble in hexane.…”
Section: Synthesis and Structurementioning
confidence: 99%